High-density silicon carbide material and preparation method thereof

By adjusting the particle grading and adding auxiliary materials of silicon carbide powder, the problem of poor performance caused by unreasonable particle grading of existing silicon carbide sintered bodies is solved, and the preparation of high-density silicon carbide materials is realized, and the sintering density and performance.

CN119462158APending Publication Date: 2025-02-18LANDSON MATERIAL TECH (YANCHENG) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411606559.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing silicon carbide sintered bodies have poor performance and low production efficiency due to unreasonable particle grading.

Method used

By adjusting the grading of silicon carbide powder particles in the base material, using four powders of different particle sizes for mixing, combining the use of graphite, carbon black and specific additives, a high-density silicon carbide material was prepared.

Benefits of technology

The overall bulk density and sintering density of silicon carbide are improved, hardness, strength, elastic modulus, creep resistance and chemical corrosion resistance are improved, and the sintering temperature is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462158A_ABST
    Figure CN119462158A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of silicon carbide materials, in particular to a high-density silicon carbide material and a preparation method thereof.The high-density silicon carbide material is prepared from, by weight, 90-96 parts of base materials, 2.5-3 parts of auxiliary materials, 1-2 parts of additives and 8-15 parts of deionized water, and the base materials are composed of silicon carbide powder a, silicon carbide powder b, silicon carbide powder c and silicon carbide powder d; the particle size of D50 in the silicon carbide powder a is 70-180 [mu] m, the particle size of D50 in the silicon carbide powder b is 25-70 [mu] m, the particle size of D50 in the silicon carbide powder c is 8-25 [mu] m, and the particle size of D50 in the silicon carbide powder d is 3-8 [mu] m. By adjusting the grain composition of the silicon carbide powder in the base material and mixing four kinds of powder with different grain sizes, the overall stacking density of the silicon carbide is greatly improved, so that the biscuit density is improved, finally, the sintering density is greatly improved, and the high density can be kept at the low sintering temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of silicon carbide materials, and in particular to a high-density silicon carbide material and a preparation method thereof. Background Art

[0002] Silicon carbide (SiC), a high-performance material, boasts exceptional high-temperature stability, high hardness, wear resistance, high thermal conductivity, and corrosion resistance, ensuring stable performance over long-term use in diverse operating conditions and applications. It is widely used in a variety of fields, including metallurgy, energy, electronics, semiconductors, and building materials. In metallurgy, it serves as a wear-resistant component and deoxidizer; in the energy sector, it is used in gas turbine engine blades and high-performance electronic components; and in the electronics and semiconductor industries, SiC power devices improve energy conversion efficiency. Its application in the chemical industry, building materials, and other fields also benefits from its excellent high-temperature tolerance and chemical stability.

[0003] Reaction-sintered silicon carbide is produced by mixing, drying, and machining raw materials (typically silicon carbide powder, graphite, carbon black, a binder, and various additives) before reacting at high temperatures (generally 1600-1800°C) to achieve densification and ultimately produce a sintered body with near-net-size dimensions. Reaction-sintered silicon carbide products, due to their excellent physical properties, unique sintering process, wide range of applications, and environmental and sustainability advantages, are playing an increasingly important role in modern industry. With the increasing demand for silicon carbide performance across various industries, the research and development of high-density reaction-sintered silicon carbide products is becoming increasingly important. The particle size distribution of the powder has the most significant impact on the density of reaction-sintered silicon carbide. Optimizing the particle size distribution can increase the sintered density, refine the grain size, and reduce voids and defects in the sintered body, thereby improving the microstructure and properties of the sintered body. Clearly, a reasonable particle size distribution in the reaction-sintering formula is clearly instrumental in improving the density of silicon carbide products.

[0004] The current unreasonable particle grading of silicon carbide powder leads to low green body density, which in turn causes low sintered density and affects its strength. If there are too many coarse particles in the mixture, the contact area between the particles will be reduced during the sintering process, making it difficult to form a dense sintered body, increasing the porosity of the sintered body, and thus reducing the sintered density and strength. Although fine particles can fill the gaps between coarse particles, too many fine particles may cause over-burning and agglomeration during the sintering process due to excessive surface activity, resulting in cracks or deformation in the sintered body, which also affects the sintered density.

[0005] Therefore, there is an urgent need to develop a high-density silicon carbide material based on a new particle grading and a preparation method thereof. Summary of the Invention

[0006] The purpose of the present invention is to provide a high-density silicon carbide material and a preparation method thereof, so as to solve the problem that the existing silicon carbide sintered body has poor sintered body performance and low production efficiency due to unreasonable particle grading.

[0007] The scheme of the present invention is:

[0008] A high-density silicon carbide material, characterized by being made of the following substances in parts by weight:

[0009]

[0010] The base material is composed of silicon carbide powder a, silicon carbide powder b, silicon carbide powder c, and silicon carbide powder d. The D50 particle size of silicon carbide powder a is 70 μm to 180 μm, the D50 particle size of silicon carbide powder b is 25 μm to 70 μm, the D50 particle size of silicon carbide powder c is 8 μm to 25 μm, and the D50 particle size of silicon carbide powder d is 3 μm to 8 μm.

[0011] The auxiliary materials are graphite and carbon black;

[0012] The additive is at least one of sodium carboxymethyl cellulose, N-methyl pyrrolidone and phenolic resin.

[0013] As a preferred technical solution, the mass ratio of the silicon carbide powder a, silicon carbide powder b, silicon carbide powder c, and silicon carbide powder d is 41.4:27.6:18.6:12.4.

[0014] As a preferred technical solution, the mass ratio of the graphite to carbon black is 0.8:2.1.

[0015] As a preferred technical solution, the mass ratio of sodium carboxymethyl cellulose, N-methyl pyrrolidone, and phenolic resin is 0.34:0.21:2.4.

[0016] As a preferred technical solution, the amount of deionized water used is 1 / 10 of the total mass of the base material, auxiliary materials and additives.

[0017] As a preferred technical solution, the steps of the preparation method of the material are as follows:

[0018] 1) Add the base material, auxiliary materials and additives to deionized water in sequence while stirring, and stir after adding;

[0019] 2) After stirring, the mixed material is placed in a sealed plastic bag for aging;

[0020] 3) The aged material is squeezed out, dried in the shade, and then processed into a shape, and sintered to obtain a high-density silicon carbide product.

[0021] As a preferred technical solution, cooling circulating water is used for cooling during the stirring process to ensure that the temperature of the mixed material is lower than 28° C., and the stirring time is 4 hours.

[0022] Compared with the prior art, the present invention has the following beneficial effects: by adjusting the particle size distribution of silicon carbide powder in the base material and using four powders of different particle sizes for mixing, the overall bulk density of silicon carbide is greatly improved, thereby increasing the density of the green body, and ultimately greatly improving the sintered density. Moreover, a high density can be maintained even at a lower sintering temperature. The hardness, strength, elastic modulus, creep resistance and chemical corrosion resistance of the obtained high-density silicon carbide product are further improved, facilitating product promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0024] In order to make the technical means, creative features, objectives and effects achieved by the present invention easier to understand, the present invention is further described below in conjunction with specific embodiments.

[0025] Example 1

[0026] The wt% of silicon carbide powder a with a D50 of 90 μm is 41.4%, the wt% of silicon carbide powder b with a D50 of 25 μm is 27.6%, the wt% of silicon carbide powder c with a D50 of 8 μm is 18.6%, and the wt% of silicon carbide powder d with a D50 of 3 μm is 12.4% (the above wt% accounts for the overall proportion of silicon carbide powder) are mixed and added to deionized water. After stirring for 10 minutes, 2.1% of carbon black and 0.8% of graphite are added. After stirring for 10 minutes, 0.34% of sodium carboxymethyl cellulose, 2.4% of phenolic resin and 0.21% of N-methylpyrrolidone are added (the above additives account for the total amount of silicon carbide powder and additives). The mixture is stirred in a mixer for 4 hours. The mass of deionized water is 1 / 10 of the total mass of each raw material.

[0027] During the mixing process, cooling water is circulated to ensure the material temperature is below 28°C. After mixing, the uniformly mixed material is placed in a sealed plastic bag for aging. The aging material is extruded, dried in the shade, and then processed into a shape. Sintering produces a high-density silicon carbide product. Shade drying is performed at 20°C and 35% relative humidity for 48 hours, and drying is performed at 65°C and 24% relative humidity for 24 hours. The processed shape can be machined.

[0028] The sintering is carried out at 1700°C for 2 hours, and a high-density silicon carbide product is obtained after the sintering is completed.

[0029] Example 2

[0030] The weight percentage of silicon carbide powder a with a D50 of 70 μm is 41.4%, the weight percentage of silicon carbide powder b with a D50 of 25 μm is 27.6%, the weight percentage of silicon carbide powder c with a D50 of 8 μm is 18.6%, and the weight percentage of silicon carbide powder d with a D50 of 3 μm is 12.4% (the above weight percentage is the overall percentage of silicon carbide powder), the weight percentage of carbon black is 2.1%, the weight percentage of graphite is 0.8%, the weight percentage of 4% sodium carboxymethyl cellulose, 2.4% wt% phenolic resin and 0.21% wt% N-methylpyrrolidone (the above additives are the proportion of the total amount of silicon carbide powder and additives), the above raw materials are mixed in deionized water in a mass ratio of 10:1, placed in a mixer and stirred for 4 hours. During the stirring process, the cooling circulating water is turned on to ensure that the material temperature is lower than 28°C. After the stirring is completed, it is completed by aging-molding-machining-sintering.

[0031] Example 3

[0032] The weight percentage of silicon carbide powder a with a D50 of 180 μm is 41.4%, the weight percentage of silicon carbide powder b with a D50 of 70 μm is 27.6%, the weight percentage of silicon carbide powder c with a D50 of 25 μm is 18.6%, and the weight percentage of silicon carbide powder d with a D50 of 3 μm is 12.4% (the above weight percentage is the total weight percentage of silicon carbide powder), the weight percentage of carbon black is 2.1%, the weight percentage of graphite is 0.8%, and the weight percentage of 0. 34% sodium carboxymethyl cellulose, 2.4% phenolic resin and 0.21% N-methylpyrrolidone by weight (the above additives are the proportion of the total amount of silicon carbide powder and additives), the above raw materials are mixed in deionized water in a mass ratio of 10:1, placed in a mixer and stirred for 4 hours. During the stirring process, the cooling circulating water is turned on to ensure that the material temperature is lower than 28°C. After the stirring is completed, it is completed by aging-molding-machining-sintering.

[0033] Example 4

[0034] The weight percentage of silicon carbide powder a with a D50 of 180 μm is 41.4%, the weight percentage of silicon carbide powder b with a D50 of 70 μm is 27.6%, the weight percentage of silicon carbide powder c with a D50 of 25 μm is 18.6%, and the weight percentage of silicon carbide powder d with a D50 of 8 μm is 12.4% (the above weight percentages are the overall percentages of silicon carbide powder), the weight percentage of carbon black is 2.1%, the weight percentage of graphite is 0.8%, and the weight percentage of 0. 34% sodium carboxymethyl cellulose, 2.4% phenolic resin and 0.21% N-methylpyrrolidone by weight (the above additives are the proportion of the total amount of silicon carbide powder and additives), the above raw materials are mixed in deionized water in a mass ratio of 10:1, placed in a mixer and stirred for 4 hours. During the stirring process, the cooling circulating water is turned on to ensure that the material temperature is lower than 28°C. After the stirring is completed, it is completed by aging-molding-machining-sintering.

[0035] The density parameters of silicon carbide products with different particle size distributions in the above examples are shown in the following table.

[0036] Table 1

[0037] Example 1 Example 2 Example 3 Example 4 <![CDATA[Powder bulk density g / cm 3 > 2.348 2.536 2.657 2.764 <![CDATA[Green body density g / cm 3 > 2.163 2.187 2.204 2.305 <![CDATA[Sintered density g / cm 3 > 3.032 3.056 3.068 3.098

[0038] From the above density test data, it can be seen that silicon carbide powder with reasonable particle size distribution can form a more compact stacking structure during the sintering process, reduce porosity, and increase the density of the sintered body. This helps to improve the mechanical properties and corrosion resistance of the product. By adjusting the particle size distribution and selecting powders of different particle sizes, the bulk density of the powder can be increased from 2.348g / cm 3 Increased to 2.764g / cm 3 The green density is from 2.163g / cm 3 Increased to 2.305g / cm 3 , sintered density from 3.032g / cm 3 Increased to 3.098g / cm3. The density of silicon carbide is greatly improved, expanding the application of reaction-sintered silicon carbide products. The performance parameters of the high-density silicon carbide product in the above embodiment are as follows:

[0039] Table 2: Performance display of silicon carbide products with different grades

[0040] Example 1 Example 2 Example 3 Example 4 Maximum sintering temperature / ℃ 1700℃ 1700℃ 1700℃ 1700℃ <![CDATA[Sintered density g / cm 3 > 3.032 3.056 3.068 3.098 Maximum sintering temperature / ℃ 1700℃ 1700℃ 1700℃ 1600℃ <![CDATA[Sintered density g / cm 3 > 3.032 3.056 3.068 3.086

[0041] From the above data, it can be concluded that by adjusting the particle size distribution of the reaction-sintered silicon carbide powder, the sintering density can be increased while the sintering temperature can be reduced. In Example 4, when the maximum sintering temperature is reduced to 1600°C, the sintering density still remains at a maximum of 3.086 g / cm 3 .

[0042] Silicon carbide powder with reasonable particle size distribution can not only form a more compact stacking structure during sintering, reduce porosity and improve the density of the sintered body, but also promote effective contact and diffusion between particles during sintering, thereby potentially reducing the required sintering temperature.

[0043] The basic principles, main features, and advantages of the present invention are shown and described above. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are merely illustrative of the principles of the present invention. Various changes and modifications may be made to the present invention without departing from the spirit and scope of the present invention. Such changes and modifications are intended to fall within the scope of the present invention. The scope of protection claimed in the present invention is defined by the appended claims and their equivalents.

Claims

1. A high-density silicon carbide material, characterized in that: Made from the following materials in parts by weight: The base material is composed of silicon carbide powder a, silicon carbide powder b, silicon carbide powder c and silicon carbide powder d, wherein the D50 particle size of silicon carbide powder a is 70 μm to 180 μm, the D50 particle size of silicon carbide powder b is 25 μm to 70 μm, the D50 particle size of silicon carbide powder c is 8 μm to 25 μm, and the D50 particle size of silicon carbide powder d is 3 μm to 8 μm; The auxiliary materials are graphite and carbon black; The additive is at least one of sodium carboxymethyl cellulose, N-methyl pyrrolidone and phenolic resin.

2. A high-density silicon carbide material according to claim 1, characterized in that: The mass ratio of the silicon carbide powder a, silicon carbide powder b, silicon carbide powder c, and silicon carbide powder d is 41.4:27.6:18.6:12.

4.

3. A high-density silicon carbide material according to claim 1, characterized in that: The mass ratio of the graphite to the carbon black is 0.8:2.

1.

4. A high-density silicon carbide material according to claim 1, characterized in that: The mass ratio of the sodium carboxymethyl cellulose, N-methyl pyrrolidone and phenolic resin is 0.34:0.21:2.

4.

5. The high-density silicon carbide material according to claim 1, characterized in that: The amount of deionized water used is 1 / 10 of the total mass of the base material, auxiliary materials and additives.

6. A high-density silicon carbide material according to any one of claims 1 to 5, characterized in that: The steps of the preparation method of the material are as follows: 1) Add the base material, auxiliary materials and additives into deionized water in sequence while stirring, and stir after adding; 2) After stirring, the mixed material is placed in a sealed plastic bag for aging; 3) The aged material is squeezed out, dried in the shade and processed into a shape, and sintered to obtain a high-density silicon carbide product.

7. A high-density silicon carbide material according to claim 6, characterized in that: During the stirring process, cooling circulating water is used for cooling to ensure that the temperature of the mixed material is lower than 28° C. and the stirring time is 4 hours.

Citation Information

Patent Citations

  • High-strength silicon carbide ceramic pipe and manufacturing method thereof

    CN105461306A

  • Silicon carbide composite powder for additive manufacturing and preparation method thereof

    CN114230346A

  • Manufacturing Method of Silicon Carbide Ceramic Seals byLiquid Phase Reaction Sintering

    KR1020000067656A

  • Silicon carbide-graphite composite material and process for producing same

    US4690909A